2017
DOI: 10.1038/s41598-017-06668-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydrophobic polymers with model lipid bilayers

Abstract: The interaction of nanoscale synthetic materials with cell membranes is one of the key steps determining nanomaterials’ toxicity. Here we use molecular simulations, with atomistic and coarse-grained resolution, to investigate the interaction of three hydrophobic polymers with model lipid membranes. Polymer nanoparticles made of polyethylene (PE), polypropylene (PP) and polystyrene with size up to 7 nm enter easily POPC lipid membranes, localizing to the membrane hydrophobic core. For all three materials, solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 33 publications
5
51
0
Order By: Relevance
“…Our results show that the phasemodifying character of certain solutes correlates with the difference in transfer free energies between competing lipid environments and that partitioning to the bilayer midplane (z min < 0.5 nm) is crucial to produce any alteration to the phase separation. Specifically, we found that dimers that partition to the midplane of the Ld phase act as domain stabilizers, while dimers that partition to the midplane of the Lo phase enhance lipid mixing, in agreement with previous simulation studies (22,24,26,27). By migrating to the DLiPC midplane, stabilizing compounds can occupy regions of the membrane inherently more disordered and where more space is available for localization, ultimately acting as domain stabilizers.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results show that the phasemodifying character of certain solutes correlates with the difference in transfer free energies between competing lipid environments and that partitioning to the bilayer midplane (z min < 0.5 nm) is crucial to produce any alteration to the phase separation. Specifically, we found that dimers that partition to the midplane of the Ld phase act as domain stabilizers, while dimers that partition to the midplane of the Lo phase enhance lipid mixing, in agreement with previous simulation studies (22,24,26,27). By migrating to the DLiPC midplane, stabilizing compounds can occupy regions of the membrane inherently more disordered and where more space is available for localization, ultimately acting as domain stabilizers.…”
Section: Resultssupporting
confidence: 90%
“…The Martini force field (19,20) represents a popular choice for studying complex membranes, as demonstrated by a recent review on this topic (21). Using the Martini force fields (19,20), several computational studies have already investigated the effect of adding specific compounds such as transmembrane peptides (22,23), amphiphiles (24) as well as small hydrophobic molecules and polymers (25)(26)(27) to ternary membranes displaying phase separation. Various possible explanations for the underlying mechanism of domain modulation by small additives have also been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] We studied PP, which is a hydrophobic polymer. [36,41] The result of our experiments is consistent with the literature. The diffusion of metal ions is slower in the water-saturated polymer compared T A B L E 3 Me 2+ uptake of polypropylene (PP).…”
Section: Discussionsupporting
confidence: 92%
“…23 There are also computational studies where partitioning of hydrophobic alkanes and polymers in the bilayer interior has been reported. 24 Although there are numerous examples on partitioning of both small and large drug molecules into the lipid membranes, 25 there is no simple explanation for KC2 separation from PC lipids.…”
Section: Resultsmentioning
confidence: 99%